Hyperthermic Intraperitoneal Chemotherapy Following Cytoreductive Surgery Improves Outcome in Patients With Primary Appendiceal Mucinous Adenocarcinoma: A Pooled Analysis From Three Tertiary Care Centers. (12th June 2015) - Shaib, Walid L.; Martin, Ludmila Katherine; Choi, Minsing; Chen, Zhengjia; Krishna, Kavya; Kim, Sungjin; Brutcher, Edith; Staley, Charles; Maithel, Shishir K.; Philip, Philip; Abdel‐Misih, Sherif; Bekaii‐Saab, Tanios S.; et al.
Abstract : Purpose: Appendiceal mucinous neoplasms (AMN) are a rare heterogeneous group of diseases. In the absence of randomized trials, AMN management is controversial. The goal of this study was to evaluate the impact of hyperthermic intraperitoneal chemotherapy (HIPEC) after cytoreductive surgery on survival in AMN patients. Patients and Methods: Patient data including demographics, pathology, type of therapy, and outcomes were collected from Emory University, the Ohio State University, and Wayne State University databases. One of the three centers did not use HIPEC. Statistical analysis evaluating overall survival (OS) of AMN patients was performed. Results: Between 1990 and 2010, 163 AMN patients were identified. Histology showed 60 patients had diffuse peritoneal adenomucinosis, 88 had peritoneal mucinous carcinomatosis (PMCA), and 15 had PMCA with indeterminate or discordant features. Complete surgical resection was achieved in 76 patients. HIPEC was used in 79 patients. The median OS was 77 months for patients who received HIPEC compared with 25 months for patients who did not ( p < .001). In multivariable analysis, histopathologic subtype ( p < .001), complete surgical resection ( p < .001), and HIPEC ( p < .001) were independent predictors for improved OS. A survival advantage for AMN patients treated at HIPEC‐treating centers was observed ( p = .0026). After adjusting for HIPEC therapy, no significant survival difference was observed between the non‐HIPEC‐treating center and the HIPEC‐treating centers ( p = .094). Conclusion: The addition of HIPEC to cytoreductive surgery likely provides a survival advantage and should be considered in the treatment strategy for AMN. Implications for Practice: The use of heated chemotherapy applied in the abdomen after removal of the appendiceal mucinous cancer by surgery lengthens survival of patients having this disease. Abstract : The goal of this study was to evaluate the impact of hyperthermic intraperitoneal chemotherapy (HIPEC) after cytoreductive surgery on survival in patients with appendiceal mucinous neoplasms (AMNs). The addition of HIPEC to cytoreductive surgery likely provides a survival advantage and should be considered in the treatment strategy for AMN.